The Application of Group Work in Classroom Interactions of Teaching Reading Comprehension of Students : Case Study SMP Negeri 6 Binjai - Debby Fadillah (Institute of Computer Science (IOCS), 2020)
This study deals with the application of Group Work in teaching English. The underlying objective of the study is to see whether teaching reading by using Group Work has significant difference from the students who do not apply it. In carrying out this study, the writer took 40 students of the first year of SMP Negeri 6 Binjai from two classes as the sample of her study. They were divided into two groups. The first group is experimental group was taught by using group work in reading comprehension, while the second group is controlled group, the reading text was taught without group work. The instrument used were teacher made test based on the materials that had been taught. These test used were administrated to find out the reliability, the computation showed that the reliability of the test was 1,5. After the treatment, a post-test was applied. The results of the study shows that teaching reading comprehension by using group work is more significant than of without group work.